MATHEMATICAL MODEL OF RESOURCE-SAVING PRODUCTION TECHNOLOGY OF BAKED GOODS WITH AMARANTH FLOUR - ANASTASIA SHISHKIN; MADINA SADYGOVA; MARIA BELOVA; TATYANA KIRILLOVA (Journal of Engineering Studies and Research)
Amaranth is a promising raw ingredients enriching bakery products, in the work used grade “Flight” Saratov breeding.  The article discusses the effect of amaranth flour and the type of liquid that goes into the dough baking on the baking properties of the semi-finished product and the quality of the finished products from wheat flour with a satisfactory quality gluten. The moisture, acidity, porosity, structural and mechanical properties, gas-forming ability, lift and fermentation activity were investigated. For the manufacture of comparable samples used wheat flour, presented on the market of Saratov. Amaranth seeds of the variety “Flight” in the amount of 7, 10, 15 and 20 %. Analysis of the effect of amaranth flour on the structural and mechanical properties of the dough showed that adding 7% or more of amaranth flour significantly reduces the spreading of the dough. The index of fermentation activity of semi-finished products with the share of amaranth flour 20%, 15%, 10% and 7% was significantly higher than the control, at the beginning of fermentation. The introduction of amaranth flour in an amount of 7 to 20 % had a significant impact on the gas-forming ability of the wheat-amaranth dough and was characterized by an intense, “explosive” beginning of fermentation and a fairly rapid decline in fermentation intensity over time, especially in a sample with a share of amaranth flour 7 %. Kneading on goat milk whey had a positive effect on the studied parameters. According to the research results, the expediency of using flour from amaranth variety Flying in the technology of bakery products made from wheat flour with a satisfactory weak gluten in quality to give them functional properties has been proved. Based on the mathematical model, the optimal parameters of the process are determined: the amount of amaranth flour in the recipe for buns is 15 %, fermentation time - 85 min, dough kneading liquid - goat milk serum.